Building Monitoring and Evaluation Capacity in the Republic of Yemen - Ivins, Ingrid; Hwang, Helena (World Bank, Washington, DC, 2014)
This note disseminates key lessons learned from the World Bank financed project in the Republic of Yemen, monitoring and evaluation of the poverty reduction strategy paper and reform programs, which established and operationalized a poverty reduction strategy monitoring unit. The approaches used, such as a study tour to Uganda, focused international training sessions, and the successful work on improving and minimizing the number of indicators, provide some lessons learned for other countries seeking to build monitoring and evaluation (M&E) capacity. Policy makers learned from Uganda s good practices of connecting accountability with resource allocation and of the importance of a strong and independent statistics office. The Republic of Yemen s experience also illustrates the value of having a powerful M&E champion to support such a significant initiative. Finally, the inclusion of civil society organizations in the planning process and in M&E outputs, especially on the central level and on policy matters, increased popular support and was an important factor in building M&E capacity.